Characterization of three naturally occurring lignans, sesamol, sesamolin, and sesamin, as potent inhibitors of human cytochrome P450 46A1: Implications for treating excitatory neurotoxicity - Du, Jie; Chen, Xiaodong; Zhao, Yongshun; Zhao, Tingting; Wang, Dalong; Chen, Zujia; Wang, Changyuan; Meng, Qiang; Yao, Jialin; Sun, Huijun; Liu, Kexin; Wu, Jingjing (Frontiers in Pharmacology, 2022)
CYP46A1 is a brain-specific enzyme responsible for cholesterol homeostasis. Inhibition of CYP46A1 activity serves as a therapeutic target for excitatory neurotoxicity. Sesame is a common medicine and food resource; its component lignans possess various pharmacological activities. In this study, the inhibitory effects of sesame lignans on CYP46A1 activity were investigated. Inhibition kinetics analyses revealed that sesamin and sesamolin produce mixed partial competitive inhibition of CYP46A1, while sesamol produces non-competitive inhibition. Notably, molecular simulations revealed that the sesame lignans have excellent orientations within the active cavity of CYP46A1. Importantly, the sesame lignans had high permeability coefficients and low efflux ratios. Furthermore, sesamin significantly reduced the levels of 24S-hydroxycholesterol in rat plasma and brain tissues, and down-regulated the protein expressions of CYP46A1, NMDAR2A, NMDAR2B, and HMGCR. Collectively, sesame lignans exhibit significant inhibitory effects on CYP46A1 activity, highlighting their potential therapeutic role in treating excitatory neurotoxicity.